Synthesis and thermodynamics of oligonucleotides containing chirally pure R(P) methylphosphonate linkages. - Reynolds, M A (1996)
Methylphosphonate (MP) oligodeoxynucleotides (MPOs) are metabolically stable analogs of conventional DNA containing a methyl group in place of one of the non-bonding phosphoryl oxygens. All 16 possible chiral R(P) MP dinucleotides were synthesized and derivatized for automated oligonucleotide synthesis. These dimer synthons can be used to prepare (i) all-MP linked oligonucleotides having defined R(P) chirality at every other position (R(P) chirally enriched MPOs) or (ii) alternating R(P) MP/phosphodiester backbone oligonucleotides, depending on the composition of the 3'-coupling group. Chirally pure dimer synthons were also prepared with 2'-O-methyl sugar modifications. Oligonucleotides prepared with these R(P) chiral methylphosphonate linkage synthons bind RNA with significantly higher affinity than racemic MPOs.